Diagnosis and treatment of abnormal left coronary artery originating from the pulmonary artery: A single-center experience - YAKUT, KAHRAMAN; Yakut, KAHRAMAN; Tokel, Niyazi Kursad; Ozkan, Murat; Varan, Birgul; Erdogan, Ilkay; Aslamaci, Mehmet Sait (My University, 2019)
Objective: We aimed to review symptoms, findings, surgical treatment options, short- and mid-term outcomes, and reoperation rate of patients diagnosed with of left coronary artery from the pulmonary artery (ALCAPA) of an anomalous origin in our institution.